Conscious Learning Model in Improving Students' Learning Outcomes: A Classroom Action Research at MIN 5 Bone - Ferdiansyah; Nahirah (MANDAILING GLOBAL EDUKASIA, 2025)
In the learning process, there are still many teachers who use the direct learning model with the lecture method, this makes students bored and bored during the learning process, so teachers need to vary the fun learning model according to learning so that students do not feel bored and bored. This study aims to examine the implementation of the Conscious Learning Model in improving students' learning outcomes through Classroom Action Research (CAR). The Conscious Learning Model emphasizes active student engagement, awareness in learning processes, and metacognitive strategies that enable learners to understand not only what they learn but how they learn. The research was conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The subjects of this study were students from a fifth-grade class at a public elementary school in Indonesia. Data were collected through observation, tests, and documentation to measure changes in student learning outcomes and engagement. The results indicated a significant improvement in student learning outcomes after the implementation of the Conscious Learning Model. In the first cycle, students showed moderate improvement, with several still struggling to articulate learning goals and monitor their understanding. In the second cycle, however, there was a marked increase in students' ability to plan, evaluate, and regulate their learning processes. This was evidenced by higher test scores, increased participation in classroom discussions, and more reflective learning behaviors. The study concludes that the Conscious Learning Model is an effective approach to enhance student learning outcomes, particularly when applied consistently with supportive instructional strategies and reflective teaching practices. The implications of this research suggest that integrating conscious and reflective learning activities into daily instruction can foster more meaningful and self-directed learning experiences for students.